Evaluation of Essential Newborn Care (ENC) Practices and Determinants among Midwives in Selected Healthcare Centers in Esan Central Local Government, Edo State - Joy Isioma Oboh; Osagie, Rachael Ngozi; Adeniran Adeniyi Ayobami; Macaulay Oluropo Babafemi Ph.D; Francis Adeniyi Balogun JP (RCHP); Layemo Princewill Adeoye (American Journal of Biomedicine and Pharmacy, 2024)
Newborns are highly vulnerable and require meticulous care to ensure their health and survival. However, despite the importance of essential newborn care (ENC) in reducing child mortality, it often receives inadequate attention, leading to preventable deaths. This study aimed to evaluate ENC practices among midwives in selected healthcare centers in Esan Central Local Government, Edo State, Nigeria. Objective: The study aimed to assess the demographic characteristics, ENC practices, factors influencing ENC, and determinants of ENC practice among midwives in the study area. Method of Analysis: A descriptive survey design with a cross-sectional approach was employed. A total of 300 midwives were purposively selected across various healthcare centers. Data were collected using structured questionnaires and analyzed using descriptive statistics. Results: The study revealed diverse demographic profiles among respondents, with notable percentages falling within the 20-29 (35.7%) and 30-39 (40.0%) age groups. Most deliveries were attended by skilled birth attendants (98.7%), and positive responses were observed for practices such as promoting thermal regulation (93.4%) and providing clean cord care (91.9%). However, gaps were identified in certain practices, including delayed cord clamping (14.3%) and utilization of partographs (12.5%). Factors influencing ENC practices included poor knowledge of ENC (62.5% Strongly Agree, 33.1% Agree), inadequate infection prevention and control skills (53.8% Strongly Agree, 43.1% Agree), and shortages of staff. Lack of adequate knowledge of midwifery care emerged as a significant concern (62.5% Strongly Agree). While no significant association was found between age, professional qualifications, and years of working experience with ENC practice, a borderline significant association was observed with rank. Conclusion: The study underscores the importance of addressing gaps and challenges in ENC practices among midwives. Continuous education and training programs, improved staffing levels, and interventions targeting socioeconomic disparities and cultural influences are crucial for enhancing the quality of essential newborn care delivery.